1999
DOI: 10.1021/la980941d
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir−Blodgett Films Based on Known Layered Solids:  Lanthanide(III) Octadecylphosphonate LB Films

Abstract: Several lanthanide(III) octadecylphosphonate Langmuir−Blodgett (LB) films have been prepared and characterized. Films with La3+, Ce3+, Sm3+, and Gd3+ are formed one bilayer at a time using a Y-type deposition procedure that allows the metal phosphonate continuous lattice network to crystallize during the upstroke of the film transfer. Comparison of the phosphonate IR stretching modes of the LB films to those of known model solids shows that each film is an LB analogue of the powdered solid-state lanthanide but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 31 publications
5
41
0
Order By: Relevance
“…It has previously been shown that the phosphonate (P}O) infrared stretching modes can be used to correlate the metal}phosphonate continuous lattice structures of LB "lms with those of the solid-state structures (9). The P}O stretching frequencies are very sensitive to the mode of metal bonding (9,12,13,30), and the di!erent metal phosphonate structure types give distinct P}O stretching patterns in their IR spectra. Figure 3 shows the asymmetric phosphonate ( (PO\ )) and symmetric phosphonate ( (PO\ )) stretches, occurring at 1083.9 and 978.8 cm\ for the Mn-P4 LB "lm and at 1084.9 and 958.6 cm\ for the Cd-P4 "lm, respectively.…”
Section: Structural Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been shown that the phosphonate (P}O) infrared stretching modes can be used to correlate the metal}phosphonate continuous lattice structures of LB "lms with those of the solid-state structures (9). The P}O stretching frequencies are very sensitive to the mode of metal bonding (9,12,13,30), and the di!erent metal phosphonate structure types give distinct P}O stretching patterns in their IR spectra. Figure 3 shows the asymmetric phosphonate ( (PO\ )) and symmetric phosphonate ( (PO\ )) stretches, occurring at 1083.9 and 978.8 cm\ for the Mn-P4 LB "lm and at 1084.9 and 958.6 cm\ for the Cd-P4 "lm, respectively.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…A variety of metal phosphonate LB "lms have been formed (7}9, 12,13) each possessing a known solid-state metal phosphonate structure type. LB "lms based on octadecylphosphonic acid (ODPA) with formulas M''(O PR)H O (M''"Mn>, Cd>, Co>, and Mg>) (9,12), M''(HO PR) (M''"Ca> or Ba>) (9,12), and¸n'''H(O PR) (¸n'''"La>, Ce>, Sm>, and Gd>) (12,13) have been prepared, where the inorganic network has the same structure as the analogous solidstate metal phosphonate of the same formula (10, 14 }17 continuous lattice structure (M''"Mn or Cd), and the magnetic properties of the manganese "lm are reported. These "lms are referred to as Mn-P4 and Cd-P4, where the P represents an alkoxyphenyl group and the 4 indicates the number of carbons separating the aryl group from the phosphonate head group.…”
Section: Introductionmentioning
confidence: 99%
“…7. The absorption bands at 1223 and 1001 cm À 1 appearing in the spectrum of HP, correspond to the PMO stretch vibrations of free phosphate and hydrogen bonding species, respectively [17,18]. The band at 1223 cm À 1 is weaker than the band at 1001 cm À 1 , indicating that most HP molecules form hydrogen bonds in the pure HP film.…”
Section: Ir Spectra Of Casting Filmsmentioning
confidence: 99%
“…Fanucci and Talham prepared several metal phosphonate LB films based upon solid-state lanthanide (III) phos- phonates by Y-type deposition procedure; photoluminescent properties were investigated showing structural films characteristics [8].…”
Section: Introductionmentioning
confidence: 99%